Real exchange-rate changes in the European Community: The empirical evidence and its implications for European currency unification - Roland Vaubel (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1976)
Is the European Community (EC) (already) a desirable currency area? There are two kinds of reasons why it may not. The first reason is that national propensities to inflate may be too different within the EC to permit the aboundonment of exchange-rate changes. Nominal exchange-rate changes are required to make differences in national monetary policies possible as well as to compensate for the resulting differences in the prices of tradable goods and services. The argument is political rather than economic in nature; what is in doubt is essentially the political will of member governments to agree en a common rate of inflation and not so much the economic feasability of such a procedure. - However, there are also economists who have argued that harmonisatian of national inflation rates is likely to produce economic losses, i.e. needless unemployment in sane member countries and needless inflation in others. The assumption that is common to them is that there is a long-run trade -off between inflation and unemployment and that this trade-off (the so-called Phillips curve) is different in different member countries. The validity of these Keynesian assumptions is disputed by modern monetarist theory and refuted by the experience of inflation in this decade: as money illusion is eroded in the process of inflation, the trade-off disappears Governments, it is true, may still be under the Phillips illusion. But this is not to say that inflationrate differentials in the 'Community are an economic rather than a political obstacle to currency unification.
Keywords: 330